Development of an in vitro carcinogenesis model of human papillomavirus‐induced cervical adenocarcinoma. Issue 3 (30th December 2021) - Zhang, Mengzhu; Kiyono, Tohru; Aoki, Kazunori; Goshima, Naoki; Kobayashi, Shin; Hiranuma, Kengo; Shiraishi, Kouya; Saya, Hideyuki; Nakahara, Tomomi
Abstract: Cervical adenocarcinoma (ADC) is the second most common pathological subtype of cervical cancer after squamous cell carcinoma. It accounts for approximately 20% of cervical cancers, and the incidence has increased in the past few decades, particularly among young patients. The persistent infection of high‐risk human papillomavirus (HPV) is responsible for most cervical ADC. However, almost all available in vitro models are designed to study the carcinogenesis of cervical squamous cell carcinoma. To gain better insights into molecular background of ADC, we aimed to establish an in vitro carcinogenesis model of ADC. We previously reported the establishment of an in vitro model for cervical squamous cell carcinoma by introducing defined viral and cellular oncogenes, HPV16 E6 and E7, c‐MYC, and activated RAS to human cervical keratinocytes. In this study, the expression of potential lineage‐specifying factors and/or SMAD4 reduction was introduced in addition to the defined four oncogenes to direct carcinogenesis toward ADC. The cell properties associated with the cell lineage were analyzed in monolayer and organoid cultures and the tumors in mouse xenografts. In the cells expressing Forkhead box A2 (FOXA2), apparent changes in cell properties were observed, such as elevated expression of columnar cell markers and decreased expression of squamous cell markers. Strikingly, the histopathology of tumors expressing FOXA2 resembled cervical ADC, proposing that FOXA2 plays a vital role in dictating the histopathology of cervical cancers. Abstract : FOXA2 plays a pivotal role in directing adenocarcinoma development of human papillomavirus‐driven cervical cancer.